Invasive squamous cell carcinoma of the hand in a patient with Kindler syndrome: Case report and literature review - Cardin-Langlois, Etienne (Pulsus Group Inc, 2010)
Kindler syndrome is a rare, autosomal, recessive genodermatosis characterized by trauma-induced acral blisters in infancy and childhood, photosensitivity and progressive poikiloderma. Very few cases in the literature report an association with squamous cell carcinoma, even though it is a very well-known, long-term complication. A case involving a 23-year-old woman with a history of Kindler syndrome who was admitted to the department of plastic surgery (Sherbrooke University, Sherbrooke, Quebec) with an extensive ulcerated squamous cell carcinoma of the right hand is presented. A local excision of the tumour was initially performed, but positive margins and clinically palpable axillary lymphadenopathy over the course of hospitalization necessitated below-elbow amputation and lymph node dissection. To the authors’ knowledge, this is the second reported case of aggressive metastatic squamous cell carcinoma of the hand in a patient with Kindler syndrome.